Conceptualising HE educators’ capabilities to teach the crisis: towards critical and transformative environmental pedagogies - Owens, John; Greer, Kate; King, Heather; Glackin, Melissa (Frontiers in Education, 2023)
This article aims to help conceptualise the capabilities that educators in higher education (HE) have to incorporate concerns about environmental breakdown in their day-to-day teaching. A common view amongst those in the academic literature is that Higher Education Institutions (HEIs) are failing to rise to the challenge presented by the unfolding environmental crisis. While agreeing that those in HE must do more, this article critically examines the assumption that such action can be easily enacted by HE educators. Our analysis employs the capabilities approach (CA) to illuminate the challenges surrounding HE educators' agency to teach the crisis in their day-to-day practice, and to consider what would be needed to provide them with genuine opportunities to do so.We argue that access to the growing number of teaching resources about the environmental crisis is a necessary but insufficient condition for supporting HE educators' capabilities to teach the crisis. For a fuller understanding of what is required to support the agency of HE educators, attention must be paid to the diverse combination of factors that shape HE educators' opportunities to develop and enact critical and transformative environmental pedagogies in their disciplinary and institutional contexts. Drawing on the extant academic literature and with reference to a fictionalised case study we examine how HE educators' agency is mediated by a range of personal, material and social factors. Our analysis focuses especially on the role played by social factors, including the influence of: dominant epistemological, methodological and disciplinary norms; prevailing institutional policies and practices, and; administrative and management cultures within and across HE. After discussing the importance that deliberation has in supporting educators' agency and the development of novel forms of critical and transformative environmental pedagogy, we conclude by suggesting that in many cases enacting such pedagogies will involve confronting dominant forms of power, culture, policy and practice, within the academy and beyond.